Microwave-induced substitutional-combustion reaction of Fe3O4/Al ceramic matrix porous composite - Lee, Chang Chuan; Yoshikawa, N.; Taniguchi, S. (Springerlink, 2011)
Link to publisher's homepage at http://www.springerlink.com